Perencanaan Kawasan Kopi di Bengkulu (Analisis Keterlibatan Petani dan Peran Pemerintah) - Fery Murtiningrum; Melinda Noer; Sri Wahyuni; Dodi Devianto (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Effective development planning is essential for achieving economic and agricultural goals, including developing coffee-growing areas. However, research on the role of farmers in this process remains limited. This study examines the planning process for coffee-growing area development in Bengkulu Province and the extent of farmer involvement in the process. The research was conducted in Kepahiang and Rejang Lebong Regencies in 2024, purposively selected as the two largest coffee-producing regions in Bengkulu. A total of 110 farmers from Kepahiang and 227 from Rejang Lebong were chosen through simple random sampling. The study analyzed variables related to the planning process, farmer empowerment through data access (including access to information, participation, inclusivity, and local institutional capacity), and community perceptions measured using a Likert scale. Findings indicate that the government plays a central role as the leading sector in coffee area development. Meanwhile, farmer groups primarily propose activities, provide data, and implement planned programs. Farmer participation mainly involves data collection and program preparation. Meetings provide equal opportunities for farmers to voice their opinions, with no restrictions on participation in group activities or discussions with agricultural offices and extension workers. Additionally, local institutions, particularly farmer groups, facilitate integrating farmers into the planning process. The study highlights the need for more substantial farmer involvement and institutional support to improve planning effectiveness and ensure sustainable coffee area development. Strengthening collaboration between government agencies, farmer organizations, and agricultural extension workers is recommended to enhance decision-making, increase inclusivity, and improve long-term development outcomes. Policies encouraging active farmer participation and institutional capacity-building will be crucial for achieving sustainable and equitable development in coffee-growing areas.